Acute Pancreatitis Secondary to Gestational Hypertriglyceridaemia - Alexis M. Cahalane; Myles J. Smith; James Ryan; Donal Maguire (Case Reports in Medicine)
Gestational hypertriglyceridaemia is a rare cause of acute pancreatitis. Its pathophysiology is incompletely understood. Severity scoring and effective management remain challenging. We report a case of acute pancreatitis secondary to gestational hypertriglyceridaemia. We describe the use of computed tomography to provide an alternative determination of severity, as well as plasmapheresis as a means of treating the condition.